Пограниччя культур: «Просвіта» як оберіг національної культури українців (на прикладі Кременецького повіту) - Скакальська, Ірина; Skakalska, Iryna (My University, 2016)
У статті розкрито полікультурне середовище Кременеччини в міжвоєнний період ХХ ст. Визначено роль «Просвіти» в збережені архетипу українців (на прикладі Кременецького повіту Волинського воєводства). Проаналізовано напрями діяльності товариства та чинники, які перешкоджали роботі просвітян. Досліджено, що просвітянська праця мала значний вплив на формування національної свідомості українського народу.In the article the multicultural environment of the Kremenets Area in the interwar period of the XXth century is revealed. The borderlands of cultures and their mutual influence are outlined. The role of the «Prosvita» Society in saving of the Ukrainian archetype (on the case of Kremenets Powiat of Volyn Voivodeship) is determined. The directions of the society’s activity and factors that impeded the work of its members are analyzed. It is investigated that with the work of the movement has influenced the formation of Ukrainian people’s national consciousness.
The Borderlands of Cultures: the «Prosvita» as a Amulet of Ukrainian National Culture (the Case of Kremenets Powiat)
Keywords: «Просвіта»; культура; національна ідентичність; освіта; Кременецький повіт; the «Prosvita» Society; culture; education; Ukrainians; Poles; national identity; Kremenets Powiat